Plasmapheresis Is Associated With Better Renal Outcomes in Lupus Nephritis Patients With Thrombotic Microangiopathy: A Case Series Study. Issue 18 (May 2016) - Li, Qiu-Yu; Yu, Feng; Zhou, Fu-De; Zhao, Ming-Hui
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The aim of this study was to evaluate the efficacy of plasmapheresis in patients with lupus nephritis-combined thrombotic microangiopathy (TMA) in a Chinese cohort. Clinical and therapeutic data of patients with lupus nephritis–combined TMA were collected retrospectively. A comparison between those with and without plasmapheresis was performed. Seventy patients with renal biopsy-proven TMA in lupus nephritis were treated with conventional combined corticosteroid and immunosuppressive agents as induction therapy, 9 of the 70 patients received additional plasmapheresis. The plasmapheresis group presented with more severe SLE and renal activity indices, including a significant higher ratio of neurologic disorder ( P  = 0.025), lower level of platelet count ( P  = 0.009), higher value of serum creatinine ( P  = 0.038), higher percentage of anti-cardiolipin antibodies positive ( P  = 0.001), and higher Systemic Lupus Erythematosus Disease Activity Index scores ( P  = 0.012), than that of the nonplasmapheresis group. However, the plasmapheresis group had a significant higher rate of remission and a lower ratio of treatment failure than that of the nonplasmapheresis group ( P  = 0.03). As the baseline data were significantly different between the 2 groups, the propensity score match was further designed to avoid retrospective bias. After re-analysis, the plasmapheresis group still had a significant higher rate of remission and a lower ratio of treatment failure than that of the nonplasmapheresis group ( P  = 0.018). More importantly, the plasmapheresis group had significant less composite endpoints than that of the nonplasmapheresis group ( P  = 0.005). Our study suggested that additional plasmapheresis on conventional induction therapy may benefit patients with lupus nephritis-combined TMA, which warrants further explorations.